2004
DOI: 10.1111/j.1532-849x.2004.04043.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Wear of Nano‐Composite Denture Teeth

Abstract: The nano-composite tooth was harder and more wear resistant than the acrylic teeth but not significantly different from most of the cross-linked and micro-filled composite teeth tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
103
2
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 23 publications
4
103
2
7
Order By: Relevance
“…Disk-shaped specimens, 4 mm in diameter and 2 mm in thickness, of the experimental unfilled resin and three composite resins were heat-polymerized. Vickers hardness values (HV0.3) of the unfilled resin and composite resins ranged from 21.5 to 27.3 kgf/ mm, which were similar to commercial composite resin artificial teeth 2) . Seventy-five specimens of each resin were prepared.…”
Section: Specimen Preparationmentioning
confidence: 89%
See 1 more Smart Citation
“…Disk-shaped specimens, 4 mm in diameter and 2 mm in thickness, of the experimental unfilled resin and three composite resins were heat-polymerized. Vickers hardness values (HV0.3) of the unfilled resin and composite resins ranged from 21.5 to 27.3 kgf/ mm, which were similar to commercial composite resin artificial teeth 2) . Seventy-five specimens of each resin were prepared.…”
Section: Specimen Preparationmentioning
confidence: 89%
“…A common feature of the enamel or occlusal layer of composite resin artificial teeth is its highly crosslinked structure, which exhibited little swelling even after 12 hours of immersion in methyl methacrylate (MMA) 1) . As for the wear resistance of composite resin artificial teeth, an in vitro study showed that it has been improved compared to conventional denture teeth 2) . However, it must be highlighted that wear of composite resin denture teeth varies depending on the antagonist and that greater wear is incurred with certain antagonists 3) .…”
Section: Introductionmentioning
confidence: 99%
“…Hardness is considered a material property related to wear resistance and it is usually used as an indicator of several mechanical properties of synthetic restorative materials and artificial teeth. [15][16][17] The aim of this study was to map the microhardness of nine artificial teeth brands according to depth. The null hypotheses were that all commercial brands of analyzed teeth present similar hardness and that all depths present similar hardness.…”
Section: Introductionmentioning
confidence: 99%
“…Resin composites with smaller filler particles can exhibit a smoother surface than those with larger particles after toothbrush/dentifrice abrasion 8) and finishing/polishing 9) . For dentures, nanocomposite teeth are reported to be harder and more wearresistant than the usual acrylic ones 10) . However, it is generally more difficult to achieve industrial fabrication of highly filled dental composites with smaller filler particles.…”
Section: Introductionmentioning
confidence: 99%